LAJU RESPIRASI DAN SUSUT BOBOT BUAH SALAK BALI SEGAR PADA PENGEMASAN PLASTIK POLYETHYLENE SELAMA PENYIMPANAN DALAM ATMOSFER TERMODIFIKASI - Rina Pratiwi Pudja, I.A. (Agrotekno, 2012)
Bali’s salacca is one of fruits which is perishable and isnot able to be stored for along time. To lengthen its shelf lifeand to prevent it from damage, this fruit can be packed inpolyethylene plastic which is known as modified atmospherepackaging (MAP).There were two objectives of this research. The firstobjective was to study respiration rate of Bali’s salacca fruitsin MAP. The second one was to study its weight loss duringstorage.This research used polyethylene plastic as packaging withthickness of 0.02, 0.05, and 0.08 mm. Storage time were 0, 2,4, 6, 8, 10, and 12 days at room temperature storage.The result showed that respiration rate expressed as O2and CO2 increased in the beginning, decreased in middle of,and increased again until the end of storage time. Duringstorage of this fruit in MAP showed lower weight loss thanthose of without packaging. It was found that the ticker theplastic used the lower weight loss of the fruit.
Keywords: MAP, plastic polyethylene, salaca fruits